Understanding financial management of non-profit organization in the case of, 'MaMoni Project, save the children USA' - Chowdhury, Orin (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.